Big data in astronomy: from evolution to revolution - Khalil, M.; Said, M.; Osman, H.; Ahmed, B.; Ahmed, Dalia; Younis, Naheel; Maher, B; Osama, M.; Ashmawy, M. (International Journal of Advanced Astronomy, 2019)
Big data is pushing astronomy in a new direction. Massive amounts of astronomical big data produced by the new generations of powerful instruments and simulations are exponentially gathered every day. Big data like astronomical images, infrared, microwave, ultraviolet, X-rays and gamma generated by stars, galaxies and black holes are observed by the new generations of space telescopes. It may take years to uncover the hidden signals in such data that may already hold answers to some of the fundamental questions of the universe weâ€™re seeking. In this paper, we attempt to present a short review about the astronomical big data and how can such massive data change our understanding of the universe.Â